Information dissemination model for scholars on cryptocurrencies - Husain, Ainin Soffia; Othman, Roslina (Institute of Electrical and Electronics Engineers Inc., 2018)
Our paper presents on an information dissemination model for scholars on cryptocurrencies. The objectives are to review the existing information dissemination models, identify known factors influencing information dissemination process, and propose an information dissemination model for scholars on cryptocurrencies. The research questions are on why the epidemic models could be used for understanding cryptocurrencies, what are the known factors influencing the relevant information dissemination model, and how could information spreading model on cryptocurrencies work for scholars. We explored the epidemic models and their influencing factors on cryptocurrencies through a survey of literature. We found that the epidemic model can describe the information spreading for scholars on cryptocurrencies. We have added the activities triggering the S-I-E-R model.